The socio-economic implications of introducing HYV in Bangladesh : proceedings of the international seminar held in April 1975 - Wood, G. Donald, 1938-; Huq, M. Ameerul (Bangladesh Academy for Rural Development, 1975)
On cultivation of high yielding varieties of rice.